2021
DOI: 10.2174/1573403x16666200220120226
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Effects of Metabolic Surgery on Type 2 Diabetes

Abstract: Introduction: Cardiovascular, together with renal disease, claims a significant proportion of morbidity and mortality in association with type 2 diabetes mellitus (T2DM) and obesity. To improve on the long-term renal and cardiovascular outcome, there is the incorporation of bariatric surgery (BS), which seems to be a pivotal intervention. Areas explored: Cohort studies and randomized controlled trial (RCT) research of BS among patients with T2DM, are investigated by screening, then information on renal effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 76 publications
0
1
0
Order By: Relevance
“…Peroxide and other ROS produced in vascular cells may play important roles in the pathogenesis of common vascular diseases [30,31], particularly diabetes. Longterm clinical observational studies on diabetes have revealed that, in addition to metabolic toxicity factors, protective factors may also protect the function and survival of cells involved in microvascular diseases through influencing blood glucose control [32][33][34]. Therefore, we also examined cardiac microvascular recruitment on the basis of the diastolic/systolic stress MBF ratio, as a novel diagnostic index with moderate diagnostic accuracy [35].…”
Section: Discussionmentioning
confidence: 99%
“…Peroxide and other ROS produced in vascular cells may play important roles in the pathogenesis of common vascular diseases [30,31], particularly diabetes. Longterm clinical observational studies on diabetes have revealed that, in addition to metabolic toxicity factors, protective factors may also protect the function and survival of cells involved in microvascular diseases through influencing blood glucose control [32][33][34]. Therefore, we also examined cardiac microvascular recruitment on the basis of the diastolic/systolic stress MBF ratio, as a novel diagnostic index with moderate diagnostic accuracy [35].…”
Section: Discussionmentioning
confidence: 99%
“…Bariatric surgery (BS) or metabolic surgery (MS) has emerged in the last decades as a treatment for obesity and diabetes for better life quality control by dramatically reducing weight and improving glycemic control, lipid profile, and BP [98]. There is strong and consistent evidence that obesity management can delay the progression from prediabetes to type 2 diabetes [99,100] and is highly beneficial in treating type 2 diabetes [101,102]. In people with type 2 diabetes and overweight or obesity, modest weight loss improves glycemia and reduces the need for glucoselowering medications [101][102][103], and larger weight loss substantially reduces A1C and fasting glucose and has been shown to promote sustained diabetes remission through at least 2 years.…”
Section: Bariatric (Metabolic) Surgery and Cardiovascular Disease Out...mentioning
confidence: 99%
“…Bariatric surgery including procedures like Roux-en-Y Gastric Bypass, Sleeve Gastrectomy, Laparoscopic Adjustable Gastric Banding as it is summarized by Damaskos et al . [ 9 , 10 ]. This approach improves clinically appropriate endpoints that include the remission of various comorbidities and the lowering of cardiovascular risks together with serious cardiovascular events but the emphasis should be given on appropriate patient selection with a long-term period of follow-up [ 11 ].…”
mentioning
confidence: 99%